Genetic Architecture of domestication- and improvement-related traits using a population derived from Sorghum virgatum and Sorghum bicolor - Liu, Huanhuan; Liu, Hangqin; Zhou, Leina; Lin, Zhongwei (Plant science, 2019)
The genetic basis of domestication and improvement remains largely unknown in sorghum as a typical multiple-origins species. In this study, the F2 and F3 populations derived from a cross between Sorghum virgatum and domesticated sorghum were used to study the genetic architecture of domestication- and improvement-related traits. We found that human selection had greatly reshaped sorghum through the Quantitative Trait Loci (QTLs) with large genetic effects in the traits of harvest, plant architecture and grain taste including the reduction of shattering, few branches, short plant stature and the removal of polyphenols from seed. The expansion of seed width was selected to improve the yield through accumulating small-effect QTLs. Two major QTLs of plant height (QTI-ph1 and dw1) were narrowed down into 24.5-kilobase (kb) and 13.9-kb, respectively. DNA diversity analysis and association mapping of dw1 gene suggested the functional variant (A1361 T) might originate from the same event not long time ago. Our results supported that parallel phenotypic changes across different species during domestication and improvement might share the same genetic basis, QTL × QTL interactions might not play an important role in the reshaping of traits during sorghum domestication and improvement, and offered new views on transgressive segregation and segregation distortion. Our study greatly deepens our understandings of the genetic basis of sorghum domestication and improvement.
Keywords: Quantitative Trait, Heritable; Sorghum; Genes, Plant; lokus kvantitativního znaku; Genome, Plant; Transgressive segregation; Segregation distortion; rostlinné geny; QTL × QTL interaction; genom rostlinný; Chromosomes, Plant; Seeds; Sorghum domestication; Quantitative Trait Loci; Quantitative Trait Locus (QTL); kvantitativní znak dědičný; semena rostlinná; šlechtění rostlin; mapování chromozomů; Domestication; Chromosome Mapping; chromozomy rostlin; Plant height; Plant Breeding; domestikace